(untitled) (Sport and Tourism Central European Journal, 2023)
Consumer needs are determined by numerous factors, hence their nature is very complex. Some of them are silent, which significantly limits the possibility of their exploration. These include the needs which exist subconsciously in the mind of an individual, who instinctively seeks to satisfy them, and the needs which an individual conceals (from the society), becoming a consumer of unusual or controversial products. The aim of this article is to assess the level of interest in selected controversial types of tourism, which make up a large part of the purchase behaviour of modern consumers. The gap in research on this subject prompts attempts to provide scientific explanations for the mechanisms associated with the demand side of the tourist sector. The research methodology was based on the use of click-tracking technology. The following three types of tourism were most frequently selected by the respondents: party tourism, extreme tourism and sex tourism. Research into the specificities of the tourism market, including controversial types of tourism, can provide vital guidance for the tourist sector as to the choices made when segmenting customers and changes in the categories of products offered to potential customers. The quantitative mapping of consumer behaviour provides a relatively clear picture of how certain controversial types of tourism are perceived.